2010
DOI: 10.1073/pnas.1003528107
|View full text |Cite
|
Sign up to set email alerts
|

Direct roles of the signaling kinase RSK2 in Cdc25C activation during Xenopus oocyte maturation

Abstract: The induction of M phase in eukaryotic cell cycles requires robust activation of Cdc2/cyclin B by Cdc25, which itself is robustly activated by serine/threonine phosphorylations. Although multiple protein kinases that directly activate Cdc25C have been identified, whether the combination of different primary phosphorylations of Cdc25C is sufficient to fully activate Cdc25C has not been determined. By analyzing the GST-Cdc25C phosphorylating activity in Xenopus egg extracts, we previously defined roles of MAPK a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Among the numerous potential RSK phosphorylation sites in xCdc25C, RSK2 predominantly phosphorylates S317, T318 and/or S319 in the motif 313 KRRRSTS 319 (36). Pairwise alignment of hCdc25A, hCdc25B and hCdc25C with xCdc25C demonstrated that RSK2 phosphorylation sites in xCdc25C localize in a conserved region near the catalytic domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the numerous potential RSK phosphorylation sites in xCdc25C, RSK2 predominantly phosphorylates S317, T318 and/or S319 in the motif 313 KRRRSTS 319 (36). Pairwise alignment of hCdc25A, hCdc25B and hCdc25C with xCdc25C demonstrated that RSK2 phosphorylation sites in xCdc25C localize in a conserved region near the catalytic domain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous results demonstrated that ERK preferentially phosphorylates and activates hCdc25C in mitotic cells (32). As ERK activation does not depend on the activation of mitotic Cdk, we hypothesize that ERK is one of the initiating kinases for hCdc25C activation during G2/M transition (36). Different from ERK, the results in this study show that RSK preferentially activates hCdc25A and hCdc25B during G2/M transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSKs phosphorylate many proteins, both cytosolic and nuclear (2). The many effects of RSKs on various proteins may contribute to the observations that RSKs mediate wide-ranging cellular processes, including proliferation (68), migration (9), and invasion (1). …”
Section: Introductionmentioning
confidence: 99%
“…RSK2 is a growth-factor-regulated kinase that was reported to mediate cell cycle progression and cell proliferation in numerous cell types and organisms (Anjum and Blenis, 2008;Cho et al, 2005;David et al, 2005;Eisinger-Mathason et al, 2008;Lin et al, 2008;Romeo and Roux, 2011;Wang et al, 2010). We now report the reduced in vitro growth ability of osteoblast lacking RSK2.…”
Section: Discussionmentioning
confidence: 74%